2020
DOI: 10.1002/aet2.10519
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation Tools in Emergency Medicine: A Systematic Review of the Literature

Abstract: Objectives: Direct observation is important for assessing the competency of medical learners. Multiple tools have been described in other fields, although the degree of emergency medicine-specific literature is unclear. This review sought to summarize the current literature on direct observation tools in the emergency department (ED) setting. Methods:We searched PubMed, Scopus, CINAHL, the Cochrane Central Register of Clinical Trials, the Cochrane Database of Systematic Reviews, ERIC, PsycINFO, and Google Scho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 81 publications
(448 reference statements)
0
13
1
Order By: Relevance
“…Thus, the qualifications section may benefit from revisions using validated workplace-based assessment scales including behavioral anchoring descriptions to ensure more consistent rating by evaluators. 7,15,16 Finally, our study found no strong correlation between the qualifications and grades. Previous research has reported grade and rank inflation to occur in up to 60% of SLOEs.…”
Section: Discussioncontrasting
confidence: 70%
“…Thus, the qualifications section may benefit from revisions using validated workplace-based assessment scales including behavioral anchoring descriptions to ensure more consistent rating by evaluators. 7,15,16 Finally, our study found no strong correlation between the qualifications and grades. Previous research has reported grade and rank inflation to occur in up to 60% of SLOEs.…”
Section: Discussioncontrasting
confidence: 70%
“…When collecting data, multiple studies emphasized the need for using both quantitative and qualitative components to avoid the limitations of purely numeric-based assessments. 17,44,50,52 Obtaining substantive comments on assessment forms can be challenging, 59,60 and future research should assess strategies for increasing qualitative comments. [61][62][63] Recent studies have also described tools for evaluating the quality of workplace-based assessment comments (e.g., Completed Clinical Evaluation Report Rating tool, Quality of Assessment for Learning score).…”
Section: Discussionmentioning
confidence: 99%
“…In the global shift towards competency‐based medical education (CBME), workplace‐based assessment (WBA) tools, informed by direct and indirect observation, have become the cornerstone of assessment 1 . While many of these WBA tools have been available for some time, including the mini‐clinical evaluation exercise (mini‐CEX), clinical encounter cards, direct observation of procedural skills (DOPS), and multi‐source feedback (MSF), 2,3 WBAs have historically been criticised for their low inter‐ and intra‐rater reliability, 4 and tendency to provide right‐shifted scores. Further, a recent systematic review of direct observation tools found that most lack strong validity evidence or reliability data 3 .…”
Section: Introductionmentioning
confidence: 99%
“…While many of these WBA tools have been available for some time, including the mini‐clinical evaluation exercise (mini‐CEX), clinical encounter cards, direct observation of procedural skills (DOPS), and multi‐source feedback (MSF), 2,3 WBAs have historically been criticised for their low inter‐ and intra‐rater reliability, 4 and tendency to provide right‐shifted scores. Further, a recent systematic review of direct observation tools found that most lack strong validity evidence or reliability data 3 . Thus, many programmes have taken the implementation of CBME as opportunity to refine WBA tools and processes.…”
Section: Introductionmentioning
confidence: 99%